Vitamin D deficiency and treatment versus risk of infection in end-stage renal disease patients under dialysis: a systematic review and meta-analysis. Issue 1 (27th July 2018) - Su, Guobin; Liu, Zhuangzhu; Qin, Xindong; Hong, Xu; Liu, Xusheng; Wen, Zehuai; Lindholm, Bengt; Carrero, Juan-Jesus; Johnson, David W; Brusselaers, Nele; Stålsby Lundborg, Cecilia
ABSTRACT: Background: Infections are common and can be fatal in patients undergoing long-term dialysis. Recent studies have shown conflicting evidence associating infection with vitamin D status or use of vitamin D and have not been systematically reviewed in this population. Methods: We searched PubMed, Web of Science, Cochrane Library, Embase and three Chinese databases from inception until December 2017 for interventional [non-randomized or randomized controlled trials (RCTs)], cohort and case–control studies on levels of serum 25-hydroxyvitamin D [25(OH)D] or use of vitamin D [supplemental nutritional vitamin D or vitamin D receptor activator (VDRA)] and infection (any infection, infection-required hospitalization or infection-related death or composite) in long-term dialysis patients. We conducted a meta-analysis on the relative risk (RR) of infection and level of 25(OH)D or use of vitamin D. Results: Of 2440 reports identified, 17 studies met inclusion criteria, all with moderate quality, with 6 cohort studies evaluating 25(OH)D serum concentrations ( n = 5714) and 11 (2 RCTs and 9 observational studies) evaluating the use of vitamin D ( n = 92 309). The risk of composite infection was 39% lower relative risk [RR] 0.61 [95% confidence interval (CI) 0.41–0.89] in the subjects with high or normal levels of 25(OH)D than in those with low levels. When compared with those who did not use vitamin D, the pooled adjusted risk for composite infection was 41% lower in those who used vitamin D [RR 0.59 (95% CI 0.43–0.81)]. Conclusions: High or normal serum levels of 25(OH)D and the use of vitamin D, particularly VDRA, were each associated with a lower risk of composite infection in long-term dialysis patients.